Determinação voltamétrica de 1,4-benzodiazepínicos e dietilpropiona como adulterantes em fitoterápicos para emagrecimento - Correia, Daniele (2008)
The adulteration of phytotherapic formulations has been a common practice in many countries, since there is not an specific legislation for the control of the manufacturing and commercialization of the so called natural medicaments . In this context, the existence of analytical methodologies, which alllow the identification and quantification of possible pharmaceuticals as adulterants in these formulations is very important in the toxicological analysis. Since the possibilitiy of adulteration is very broad in terms of compound classes, the analytical methods have to be very selective and sensitve for the identification os compound classes and/or individual compounds. In this work, a voltammetric method was developed and validated for the selective determination of pharmaceuticals from the class of 1,4-benzodiazepines (ansiolytics) and diethylpropion (anorexics). In order to investigate the possible interference of other electroactive drugs (possible adulterants in phytotherapic formulations) at the mercury electrode, synthetic mixtures containing different concentrations of 1,4-benzodiazepines, diethylpropion and interferents fluoxetine, sibutramine and metformin were analyzed. The parameters of the voltammetric analysis, such as pH, potential and time of deposition, were optimized aiming a voltammetric measurement with high selectivity and sensitivity. The validated method was applied for the determination of the adulterants in phytotherapic formulations used in the treatment of obesity, which have been commercialized as natural medicaments by Brazilian pharmacies. Four different phytotherapic formulations were found to be contaminated by 1,4-benzodiazepines in concentration ranging from 0,056 to 0,270 mg/g. Recovery experiments for 1,4-benzodiazepines and diethylpropion were carried out in the formulations, which gave recovery values higher than 90% for all the analyzed adulterants. The developed and validated method presented high sensitivity, selectivity, analytical precision and short analysis time. Therefore, the method is very usefull as an analytical tool for the control and fiscalization of the adulteration of phytotherapic formulations.